Nickel-Catalysed Arylative Cyclisations of Alkynones & Molecular Editing of Cyclic Ketones - Green, Harley (2023)
PART I: NICKEL-CATALYSED ANTI-ARYLMETALLATIVE CYCLISATIONS ONTO KETONES A highly enantioselective and regioselective nickel-catalysed domino reaction of the addition of boronic acids across an alkyne, followed by subsequent cyclisation onto a ketone is reported. The reversible E/Z isomerization of the alkenylnickel intermediate is key to enable the overall anti-arylmetallative cyclisation. The process affords enantioenriched tertiary-alcohol-containing products of which the ring system is featured in several diarylindolizidine alkaloids.